(untitled) (Research, Society and Development, 2020)
This article seeks to discuss aspects related to the development of children with physical disabilities in the light of historical-cultural psychology. Our gaze will turn to play and the importance of this activity in socializing, in the experiences of discovery and in the experimentation and appropriation of cultural facts. The research will take place in three preschools in a municipality in Paraná. This is an exploratory study with a qualitative approach in which we will analyze the conceptions of teachers and professionals who provide pedagogical support to children at school, seeking to understand their conceptions about the importance of playing. We will present proposals for inclusion based on historical-cultural psychology. In the end, it is expected to contribute to the learning and interaction of these students and to facilitate the work of inclusion in these preschools.